Framework Of Information System Of IT Service Desk Using UML (Unified Modelling Language) Technique - Study Case In Republic Of Indonesia State Civil Service Agency - Melyani Melyani; Ahmad Rafik; Roydawaty Roydawaty; Indra Riyana; Rizkiana Karmelia Shaura; Hendra Kurniawan; Rahayu Swastika (University of Science and Computer Technology, 2024)
At Republic of Indonesia State Civil Service Agency in carrying out work, it is often found that problems both software and hardware are installed in the computer and must be resolved immediately. However, the handling of problems is still not good, where in the process of reporting complaints and requests, you still have to go by telephone or come directly to the IT staff office to notify complaints, as well as in manual records that affect company performance. All recording reports and problem calculations are still manual. This can have a negative effect, namely: there are problems that are at risk of being recorded repeatedly, so it takes a long time to provide reports to managers. Therefore, the authors submit a helpdesk information system application to solve the problems of complaints and employee requests so that they can be resolved quickly and can be handled properly as well as recording reports that are well recorded. In developing this helpdesk information system, the author uses an object-oriented methodology, namely the iteration waterfall, which is modeled using UML (Unified Modeling Language). The tools used are XAMPP as a web server, PHP as a programming language and MySQL as a database. With this system, it is hoped that it can make it easier for employees to report complaints as well as get solutions to the problems they are complaining about and also make it easier for IT staff to automatically generate reports in the system.